Earnings management: How Financial Distress, Sales Growth, and Audit Committees Interact - Dyah Permatasari, Maulina; Yahya, Adibah; Fatonah, Tania Nur (LPPM Universitas Pelita Bangsa, 2024)
This study aims to examine the effect of financial distress, sales growth, and audit committee on earnings management. We used a sample of manufacturing companies in Indonesia during the period 2020 – 2022. The regression results show that only sales growth has a significant influence on earnings management. The analytical method used is multiple linear regression analysis with SPSS as an analytical test tool. The analysis test is carried out through the classical assumption test, hypothesis test, and coefficient of determination test. The test results show that companies that experience high sales growth tend to perform earnings management to achieve the expected target. Meanwhile, the results found no evidence of a significant effect of financial distress and audit committee on earnings management.